2021
DOI: 10.1038/s41598-021-92830-8
|View full text |Cite
|
Sign up to set email alerts
|

Serine residues 726 and 780 have nonredundant roles regulating STAT5a activity in luminal breast cancer

Abstract: In breast cancer, prolactin-induced activation of the transcription factor STAT5a results from the phosphorylation of STAT5a tyrosine residue 694. However, its role in mammary oncogenesis remains an unsettled debate as STAT5a exhibits functional dichotomy with both pro-differentiative and pro-proliferative target genes. Phosphorylation of STAT5a serine residues, S726 and S780, may regulate STAT5a in such a way to underlie this duality. Given hematopoiesis studies showing phospho-serine STAT5a as necessary for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Similar to the results in HeLa cells, distinct single bands were detected in the normal feline mammary gland and feline mammary carcinoma lysates in the blots stained with anti-tSTAT5 antibody. For pSTAT5, although a distinct single band was detected in the normal feline mammary gland lysate, no band was detected in the feline mammary carcinoma lysate [ 20 , 56 ]. β-actin as a loading control was detected as single bands in all lysates from normal feline mammary gland, feline mammary carcinoma, and HeLa cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the results in HeLa cells, distinct single bands were detected in the normal feline mammary gland and feline mammary carcinoma lysates in the blots stained with anti-tSTAT5 antibody. For pSTAT5, although a distinct single band was detected in the normal feline mammary gland lysate, no band was detected in the feline mammary carcinoma lysate [ 20 , 56 ]. β-actin as a loading control was detected as single bands in all lysates from normal feline mammary gland, feline mammary carcinoma, and HeLa cells.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in this study, we used the anti-STAT5a antibody used in previous studies [16,56]. Furthermore, cross-reactivity of both STAT5a and pSTAT5 antibodies was confirmed by western blotting because cross-reactivity has not yet been reported in feline tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, future studies should assess the variation in breast cancer risk by pSTAT5a and pSTAT5b, particularly in premenopausal women. Additionally, we evaluated tyrosine phosphorylated STAT5, however unphosphorylated STAT5 as well as serine-phosphorylated STAT5 may have varying associations with breast cancer risk and should be considered in future studies [ 38 , 39 ]. Similarly, our assessment of PRLR did not distinguish between different isoforms of this receptor, which have been shown to have differential effects on downstream STAT5 signaling [ 40 ], suggesting that future studies should separately evaluate the most oncogenic isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…In ER-positive breast cancer, STAT5 expression enhanced the response to hormone therapy and increased the overall survival of patients [reviewed in ( 81 )]. Recent studies have shown that phosphorylation of STAT5a serine residues (S726 and S780) may regulate its activity to promote cell proliferation in MCF-7 cells ( 82 ). Reports have indicated that STAT5 acts as a suppressor of breast cancer invasion and metastatic progression and can be used as a tumor marker of favorable prognosis [reviewed in ( 79 )].…”
Section: Role Of Prl/prlr Signaling In Breast Cancermentioning
confidence: 99%